Life‐space mobility and healthcare costs and utilization in older men. Issue 8 (7th May 2021) - Sheets, Kerry M.; Kats, Allyson M.; Langsetmo, Lisa; Mackey, Dawn; Fink, Howard A.; Diem, Susan J.; Duan‐Porter, Wei; Cawthon, Peggy M.; Schousboe, John T.; Ensrud, Kristine E.
Abstract: Objectives: To determine the association of life‐space score with subsequent healthcare costs and utilization. Design: Prospective cohort study (Osteoporotic Fracture in Men [MrOS]). Setting: Six U.S. sites. Participants: A total of 1555 community‐dwelling men (mean age 79.3 years; 91.5% white, non‐Hispanic) participating in the MrOS Year 7 (Y7) examination linked with their Medicare claims data. Measurements: Life‐space during the past month was assessed as 0 (daily restriction to one's bedroom) to 120 (daily trips outside one's town without assistance) and categorized (0–40, 41–60, 61–80, 81–100, 101–120). Total annualized direct healthcare costs and utilization were ascertained during 36 months after the Y7 examination. Results: Mean total annualized costs (2020 U.S. dollars) steadily increased across category of life‐space score, from 7954 (standard deviation [SD] 16, 576) among men with life‐space scores of 101–120 to 26, 430 (SD 28, 433) among men with life‐space scores of 0–40 ( p < 0.001). After adjustment for demographics, men with a life‐space score of 0–40 versus men with a life‐space score of 101–120 had greater mean total costs (cost ratio [CR] = 2.52; 95% confidence interval [CI] = 1.84–3.45) and greater risk of subsequent hospitalization (odds ratio [OR] 4.72, 95% CI 2.61–8.53) and skilled nursing facility (SNF) stay (OR 7.32, 95% CI 3.65–14.66). Life‐space score was no longer significantly associated with total healthcare costs (CR for 0–40 vs 101–120 1.29; 95% CI 0.91–1.84) and hospitalization (OR 1.76, 95% CI 0.89–3.51) after simultaneous consideration of demographics, medical factors, self‐reported health and function, and the frailty phenotype; the association of life‐space with SNF stay remained significant (OR 2.86, 95% CI 1.26–6.49). Conclusion: Our results highlight the importance of function and mobility in predicting future healthcare costs and suggest the simple and convenient life‐space score may in part capture risks from major geriatric domains and improve identification of older, community‐dwelling men likely to require costly care.